2021
DOI: 10.19088/k4d.2021.083
|View full text |Cite
|
Sign up to set email alerts
|

Access to Climate Finance by Women and Marginalised Groups in the Global South

Abstract: This paper examines the issue of management of climate finance in the Global South. It acknowledges the efforts made by the various stakeholders so far but seeks to advance a clarion call for a more inclusive and targeted approach in dealing with climate change. The authors highlight the limited role played by least developed countries and small island developing states in contributing to the conversation on climate change. The authors emphasize the need for enhancing the role of the most vulnerable countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…2022d; Esplen 2016). Because local gender experts can provide insights into the gender and social dynamics within a given context, their participation and that of local women's groups increases the effectiveness of technical assistance, and more appropriately responds to the development and adaptation needs of a community (Price 2021;Daniel 2021). Despite this, Schalatek et al (2021) found that of the 30 GCF projects they evaluated, only 4 included plans for hiring local gender experts to assist in project implementation, and none included these experts or the national gender machinery in all aspects of the project.…”
Section: Culture and Capacitymentioning
confidence: 99%
“…2022d; Esplen 2016). Because local gender experts can provide insights into the gender and social dynamics within a given context, their participation and that of local women's groups increases the effectiveness of technical assistance, and more appropriately responds to the development and adaptation needs of a community (Price 2021;Daniel 2021). Despite this, Schalatek et al (2021) found that of the 30 GCF projects they evaluated, only 4 included plans for hiring local gender experts to assist in project implementation, and none included these experts or the national gender machinery in all aspects of the project.…”
Section: Culture and Capacitymentioning
confidence: 99%
“… 51. Smith et al (2014); also Gomez (2013); Amerasinghe et al (2017); Colenbrander et al (2018); Price (2021). …”
mentioning
confidence: 98%